2019
DOI: 10.1096/fj.201802642r
|View full text |Cite
|
Sign up to set email alerts
|

Activation of prostaglandin EP4 receptor attenuates the induction of cyclooxygenase‐2 expression by EP2 receptor activation in human amnion fibroblasts: implications for parturition

Abstract: Human amnion fibroblasts produce abundant prostaglandin E2 (PGE2), which plays a crucial role in parturition by stimulating not only myometrial contraction and cervical ripening but also the expression of the rate‐limiting enzyme in PGE2 synthesis—namely, cyclooxygenase‐2 (COX‐2). This feed‐forward induction of COX‐2 expression by PGE2 is mediated via its receptors coupled with the cAMP and PKA pathway and subsequent phosphorylation of the transcription factors cAMP‐response element binding protein (CREB) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
(81 reference statements)
2
13
0
Order By: Relevance
“…Our data further suggest that STAT3 is activated following Wnt stimulation via PGE , since the latter is produced by Wnt3a treated BMDMs ( Figure 8A) and has been shown to promote the phosphorylation of STAT3 in various cell types [46][47][48][49] . Wnt signaling promotes the production of PGE through transcriptional regulation of Ptgs2 50,51 , with similar results shown in Figure 8C.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our data further suggest that STAT3 is activated following Wnt stimulation via PGE , since the latter is produced by Wnt3a treated BMDMs ( Figure 8A) and has been shown to promote the phosphorylation of STAT3 in various cell types [46][47][48][49] . Wnt signaling promotes the production of PGE through transcriptional regulation of Ptgs2 50,51 , with similar results shown in Figure 8C.…”
Section: Discussionsupporting
confidence: 65%
“…Of the upregulated metabolites we focused on PGE 2 because of its function as an amplifier of IL-4 responses 29,[43][44][45] (Figure 8 figure supplement 1C) and its role as a STAT3 activator in various cell types [46][47][48][49] Figure 8B), despite marked differences in the IL-4 concentrations used in these experiments (0.1ng/mL and 20ng/mL , respectively).…”
Section: Wnt3a Induces the Production Of Pge 2 Which Causes The Enhmentioning
confidence: 99%
“…19,27,28 Of interest, in addition to COX-2, glucocorticoids also induce the expression of its own regenerating enzyme 11β-HSD1 in amnion fibroblasts so that a feedforward reaction for glucocorticoid regeneration and PG production is ensured toward the end of gestation in the fetal membranes in preparation for the onset of parturition. 29,30 Apart from the induction of 11β-HSD1 and COX-2 expression by glucocorticoids, [31][32][33][34] a number of other factors pertinent to parturition such as PGs and proinflammatory cytokines have also been shown to induce the expression of both 11β-HSD1 and COX-2 in amnion fibroblasts, 29,[35][36][37][38] which further illustrates the crucial roles of these genes in parturition.…”
Section: Introductionmentioning
confidence: 96%
“…We set out to delineate this paradoxical mechanism and it turned out to be a very complicated mechanism. It is revealed that glucocorticoids induce cPLA2 and COX-2 expression through stimulation of the cAMP/PKA pathway with subsequent activation of multiple transcription factors including CREB and STAT3, and so on (Zhu et al, 2009;Guo et al, 2010;Wang et al, 2015;Lu et al, 2017Lu et al, , 2019a. Interestingly, the classical inflammatory transcription factor, nuclear factor κB, is nevertheless inhibited by glucocorticoids (Guo, 2010), which is responsible for the inhibition of proinflammatory cytokine expression in human amnion fibroblasts, a situation resembling most of non-gestational tissues.…”
Section: Role Of Cortisol Regeneration In the Stimulation Of Prostaglmentioning
confidence: 99%